Efficacy and safety of lenvatinib–transcatheter arterial chemoembolisation sequential therapy followed by surgical resection for intermediate-stage hepatocellular carcinoma beyond Up-to-7 criteria: a study protocol for a multicentre, single-arm, prospective study - Hiroshi Aikata; Hiroshi Sakai; Michio Imamura; Masahiro Ohira; Tsuyoshi Kobayashi; Ryosuke Nakano; Naoki Tanimine; Shintaro Kuroda; Hiroyuki Tahara; Kentaro Ide; Hideki Ohdan; Ko Oshita; et al. (BMJ Open, 2023)
Introduction The feasibility and efficacy of surgical resection following systemic therapy for intermediate-stage hepatocellular carcinoma (HCC) beyond the Up-to-7 criteria is unclear. The combination of lenvatinib (LEN) and transcatheter arterial chemoembolisation (TACE), termed LEN–TACE sequential therapy, has shown a high response rate and survival benefit in patients with intermediate-stage HCC. This trial aims to evaluate the efficacy and safety of LEN–TACE sequential therapy and the feasibility of surgical resection for intermediate-stage HCC beyond the Up-to-7 criteria.Methods and analysis This is a multicentre, single-arm, prospective clinical trial. Thirty patients with intermediate-stage HCC beyond the Up-to-7 criteria will be enrolled. Patients eligible for this study will undergo LEN–TACE sequential therapy in which LEN is administered for 4 weeks, followed by TACE, and then further LEN for another 4 weeks. Patients will be assessed for efficacy of LEN–TACE sequential therapy and resectability, and surgical resection will be performed if the HCC is considered radically resectable. The primary outcome of this study is the resection rate after LEN–TACE sequential therapy. The secondary outcomes are the objective response rate of LEN–TACE sequential therapy, safety, curative resection rate, overall survival and recurrence-free survival.Ethics and dissemination This trial was approved by the Institutional Review Board of Hiroshima University, Japan (approval no. CRB210003), and has been registered with the Japan Registry of Clinical Trials (jRCTs061220007). The results of this study will be submitted for publication in a peer-reviewed journal and shared with the scientific community at international conferences.Trial registration number jRCTs061220007 (https://jrct.niph.go.jp/latest-detail/jRCTs061220007).